Strategi Implementasi PJBL untuk Meningkatkan Motivasi dan Hasil Belajar Siswa - Yeni Nuraeni; Wanda Adwi Kurnia; Vriska Nadilla Handayani; Kezia Citra Kirana; Siti Nailatus Syifa; Zelena Putri Dinata (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2025)
This journal studies Project Based Learning (PjBL) as one of the innovative learning strategies that use projects or activities as a means of learning to improve students' learning motivation, learning outcomes, knowledge, and skills. The method used in this study is a qualitative approach with literature studies, namely by collecting and analyzing data from various scientific journals, articles, and relevant literature that discuss PjBL, active learning strategies, student learning motivation, and achievement of learning outcomes at various levels of education, especially at the elementary school level. The results of the study show that the implementation of PjBL has proven to be effective in increasing students' learning motivation because this approach emphasizes active involvement, collaboration, a sense of responsibility, and the development of students' creativity during the learning process. More than that, this strategy allows students to learn through hands-on experience and real-world problem-solving, thus making the learning process more contextual, fun, and meaningful. In addition to increasing motivation, PjBL also contributes significantly to improving learning outcomes, because students understand the material more easily when it is associated with daily life. These findings affirm the importance of implementing project-based learning strategies as an alternative learning model relevant to the needs of the 21st century, emphasizing critical thinking, communication, collaboration, and creativity (4C) skills. Therefore, this study recommends that teachers and educators integrate the PjBL approach systematically and structurally in learning planning and in the curriculum to improve the quality of education, student involvement, and learning outcomes in a comprehensive, effective, and sustainable manner.